2022
DOI: 10.7150/jca.52943
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of metabolome and gut microbiota in Patients with pancreatic ductal adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumour with a poor prognosis and a high mortality rate. It is of great significance to explore sensitive or specific biomarkers for early diagnosis and prognosis. We first examined the metabolome and gut microbiota of resectable and unresectable PDAC patients to comprehensively investigate the characteristics of PDAC at different stages of progression. At the genus level, we found that the relative abundances of Alistipes, Anaerostipes, Faecalibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Anaerotruncus correlated with cholesterol diet-induced nonalcoholic fatty liver disease (NAFLD)-associated hepatocellular carcinoma (HCC), and a study demonstrated a progressive increase in the abundance of Anaerotruncus during the NAFLD-HCC disease process [44]. The accumulation of Anaerotruncus in the intestine increased the risk of anal stula, and Anaerotruncus was increased in unresectable pancreatic ductal adenocarcinoma (PDAC) [45]. The overexpression of granulocyte-macrophage colony-stimulating factor (GM-CSF) in hepatocellular carcinoma could reduce the abundance of Anaerotruncus in the intestine [46].…”
Section: Discussionmentioning
confidence: 99%
“…Anaerotruncus correlated with cholesterol diet-induced nonalcoholic fatty liver disease (NAFLD)-associated hepatocellular carcinoma (HCC), and a study demonstrated a progressive increase in the abundance of Anaerotruncus during the NAFLD-HCC disease process [44]. The accumulation of Anaerotruncus in the intestine increased the risk of anal stula, and Anaerotruncus was increased in unresectable pancreatic ductal adenocarcinoma (PDAC) [45]. The overexpression of granulocyte-macrophage colony-stimulating factor (GM-CSF) in hepatocellular carcinoma could reduce the abundance of Anaerotruncus in the intestine [46].…”
Section: Discussionmentioning
confidence: 99%
“…There was not any significant difference between the duodenal fluid microbiota profiles of patients with pancreatic cysts and healthy individuals. 35 Finally, more recently, Guo et al (2022) reported that microbiome variation is related to pancreatic cancer. 36…”
Section: Microbiome In Pdacmentioning
confidence: 99%
“…In 2019, Del Castillo et al reported that, the relative abundances of Fusobacterium, Porphyromonas, Capnocytophaga, idocharacter, Prevotella, Gemella and Selemonas was higher in pancreatic cancer patients when compared with healthy people 39 . The changes in microbiome in vivo are highly correlated with in cancer patients and cancer progression 36 . Future human studies are necessary to fully understand the effect of microbiome in different periods of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations